2013
DOI: 10.5812/nms.11691
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy After Life Skills Training: A Case-Control Study

Abstract: Background:Nursing students' self-efficacy is a predictor for their educational progress. Students, who believe that they can be successful in their studies, are more confident. Therefore, many universities have focused on life skills training programs to improve the mental health of their students. Objectives: This study was conducted to evaluate and compare self-efficacy in two groups of nursing students of Tehran University of Medical Sciences (TUMS). One group of students was trained on life skill programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Research conducted by [44] reported in their study that about 65% to 72% of the students had very high or high selfefficacy. Also, [23] reported that most of the nursing students in their study had a high level of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by [44] reported in their study that about 65% to 72% of the students had very high or high selfefficacy. Also, [23] reported that most of the nursing students in their study had a high level of self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Only few evidences demonstrated that these life skills trainings not always are useful (or partially useful) to increase the social and life skills (e.g. Babakhani, 2011;Rezayat & Nayeri, 2013). Likewise, Sagone, De Caroli, Indiana, & Fichera (2018) found that, after the life skills training about self-image and sociorelational competences, preadolescents enhanced their self-efficacy only in the managing of negative emotions and some factors of psychological well-being.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Clinical self-efficacy in nursing students can also reflect the educational situation of the nursing faculties. However, self-efficacy is a complex concept; research has indicated that a life skills training program did not affect the self-efficacy of nursing students ( 17 ). It seems that this important issue needs further investigation.…”
Section: Introductionmentioning
confidence: 99%